2007
DOI: 10.1055/s-2007-990262
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Method for Quantitative Determination of Total Anthocyanins and Quality Characteristics of Roselle (Hibiscus sabdariffa)

Abstract: A simple, rapid and cost-saving method for the determination of total anthocyanins in roselle has been developed. The method was based on pH-differential spectrophotometry. The calibration curve of the major anthocyanin in roselle, delphinidin 3-sambubioside (Dp-3-sam), was constructed by using methyl orange and their correlation factor. The reliability of this developed method was comparable to the direct method using standard Dp-3-sam and the HPLC method. Quality characteristics of roselle produced in Thaila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The total anthocyanin content (TAC) of purple pak-choi was quantified with a modified pH differential method (AOAC official method 2005.2) [45,46]. The TAC was derived using cyanidin-3-glucoside, which has a molar extinction coefficient of 26,900 L cm -1 mol -1 and a molecular weight of 449.2 g mol -1 .…”
Section: Methodsmentioning
confidence: 99%
“…The total anthocyanin content (TAC) of purple pak-choi was quantified with a modified pH differential method (AOAC official method 2005.2) [45,46]. The TAC was derived using cyanidin-3-glucoside, which has a molar extinction coefficient of 26,900 L cm -1 mol -1 and a molecular weight of 449.2 g mol -1 .…”
Section: Methodsmentioning
confidence: 99%
“…UKMR-2 calyces at different maturation stages. The analysis result of the total phenolic and anthocyanin contents was obtained from our previous investigation ( Figure 2) Sukwattanasinit et al 2007). The total phenolics content shows increasing progress throughout the ripening period.…”
Section: Chemical Analysismentioning
confidence: 88%
“…In addition to anthocyanins, Roselle calyces are also rich natural source of other chemical compounds including flavonoids, tannins, steroids, phenols, triterpenoids and alkaloids (Brahma et al 2014;Ijeomah et al 2012;Mungole & Chaturvedi 2011;Obouayeba et al 2014). High-Performance Liquid Chromatography (HPLC) has been widely used in the identification and quantification of anthocyanins in the Roselle extract (Kouakou et al 2015;Lislivia et al 2017;Sukwattanasinit et al 2007). Lislivia et al (2017) and Sukwattanasinit et al (2007) reported that delphinidin-3-O-sambubioside and cyanidin-3-O-sambubioside are two predominant anthocyanins that can be found in dried roselle calyces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral and chromatographic analyses showed that the isolated compound was delphinidine-3-glucoside [12]. The total anthocyan content in L. chinensis flowers was 0.14% [13].…”
mentioning
confidence: 95%